Analisis Tingkat Kepuasan Pasien Rawat Jalan Pada Pelayanan Kefarmasian Di Rumah Sakit Universitas Sebelas Maret Periode Bulan Oktober Tahun 2023 - Dzithauly Maulidiva Abadi; Endang Sri Rejeki; Avianti Eka Dewi Aditya Purwaningsih (Jurnal Farmasi & Sains Indonesia, 2025)
Pharmaceutical health services need to be considered service standards, one of which is about patient satisfaction with pharmaceutical services in hospitals. Patient satisfaction is the patient's assessment of the service delivery received. The purpose of the study was to determine the level of patient satisfaction with pharmaceutical services and determine the relationship between the level of satisfaction with the dimensions of patient satisfaction. This type of research is descriptive non-experimental with cross sectional method. The study used 100 respondents. Data collection using accidental sampling method. Data analysis used univariate tests to obtain frequency distribution of patient satisfaction levels. Simple linear regression bivariate analysis to determine the relationship between patient satisfaction level and satisfaction dimension. The patient satisfaction level of the pharmaceutical installation of Sebelas Maret University Hospital obtained reliability results of 75.25%, responsiveness 70.43%, emphty 69.16%, assurance 77%, tangible 74.87%. The relationship between service quality and the highest level of satisfaction obtained the responsiveness dimension of 0.742